Integrated Marketing Communication Strategy at the South Sulawesi Culture and Tourism Service to Increase Tourist Visits in the New Normal Era - Devy Khaddafi; Nur Alim Djalil; Andi Vita Sukmarini (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
One form of alternative tourism that is based on nature conservation and empowerment of local communities is village tourism, where the tourism development process carried out is based on exploring the potential of existing resources in the village along with empowering local communities. On this basis, the Indonesian government has begun to intensify the development of tourist villages since the last decade to address alternative tourism activities. The existence of efforts to develop tourist villages is also motivated by the government's desire to empower and improve the economy of village communities where there are still many villages that have the status of underdeveloped villages. This research approach uses a qualitative descriptive approach. This is because this research procedure produces descriptive data in the form of written or spoken words from people and observable behavior. There is a suitability or link between integrated marketing communication strategies and the increase in the number of tourist visits to South Sulawesi after the Covid-19 pandemic. Steps to restore the number of tourist visits to South Sulawesi through organizing tourism events, direct marketing and targeted publications, are the leading steps for the South Sulawesi culture and tourism department to attract tourists to South Sulawesi. Synergy and collaboration from all tourism stakeholders starting from the government, media, business world, universities and communities/society are the keys to the revival of tourism in South Sulawesi.